2010
DOI: 10.1073/pnas.1003597107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-catalyzed asymmetric additions of malonate esters to γ-substituted allenoates and allenamides

Abstract: Because carbonyl groups are ubiquitous in organic chemistry, the ability to synthesize functionalized carbonyl compounds, particularly enantioselectively, is an important objective. We have developed a straightforward and versatile method for catalytic asymmetric carbon-carbon bond formation at the γ-position of carbonyl compounds, specifically, phosphine-catalyzed additions of malonate esters to γ-substituted allenoates and allenamides. Mechanistic studies have provided insight into the reaction pathway.here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(22 citation statements)
references
References 28 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…78 Unlike previous examples, promoting efficient proton transfer required only a small amount (10 mol %) of 2-methoxyphenol and the reaction could be conducted at much lower temperatures to ensure good enantiocontrol.…”
Section: Enantioselective Phosphine Catalysismentioning
confidence: 99%
“…78 Unlike previous examples, promoting efficient proton transfer required only a small amount (10 mol %) of 2-methoxyphenol and the reaction could be conducted at much lower temperatures to ensure good enantiocontrol.…”
Section: Enantioselective Phosphine Catalysismentioning
confidence: 99%
“…Very good yields and excellent ee values are found in these reactions promoted by a chiral phosphine 272 (Scheme 160). [302] Denmark et al reported reactions of N-silyl oxyketene imines and aromatic aldehydes. The products are very valuable building blocks that are isolated in excellent enantio-as well as diastereoselectivity accompanied by very good yields.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…While various activation modes that allow for a (a 2 /d 2 ), b (a 3 ), g (d 4 ), and e (d 6 ) functionalization have been reported through secondary amine organocatalysis, [2] umpolung strategies remain elusive outwith the confines of SOMO activation [2b] and processes mediated by N-heterocyclic carbenes (NHCs). [3,4] Because pyrrolidine-and imidazolidinone-based organocatalysts require carbonyl substrates to generate the transient intermediates that are central for catalysis, the substrate scope is limited to aldehydes and ketones with varying degrees of unsaturation. With a view to extending the substrate scope of secondary-amine-catalyzed processes, and providing an entry point into the design of homologous variants of addition reactions to a,b-unsaturated iminium ions, we began exploring the reactivity of cyclopropane carbaldehydes.…”
mentioning
confidence: 99%
“…Initially, the commonly used reagents 9 and 11 were selected as the Cl À and Cl + sources, respectively. Catalyst screening using a variety of secondary amine organocatalysts (1)(2)(3)(4)(5)(6)(7)(8) quickly revealed that the firstgeneration MacMillan catalyst 5 furnished the expected 1,3-dichloride with the highest levels of diastereo-and enantiocontrol ( 9). It is important to note that no reaction is observed in the absence of a secondary amine catalyst.…”
mentioning
confidence: 99%